Comparative Study on Soil Microbial Biomass in Tarai and Hill Sal (Shorearobusta Gaertn.) Forests of Tropical Region in Eastern Nepal - Bhattarai, Krishna Prasad; Mandal, Tej Narayan (Nepal Journal of Science and Technology, 2020)
A comparative study was conducted to investigate the effect of altitudinal variation and seasonality on soil microbial biomass carbon (MB-C), nitrogen (MB-N), and phosphorus (MB-P) between Tarai Sal forest (TSF) and Hill Sal forest (HSF) of the tropical region in eastern Nepal. Soil microbial biomass was estimated by chloroform fumigation - extraction method in summer, rainy and winter seasons in the upper (0-15 cm) soil depth in both forests. Pre-conditioned soil samples were saturated with purified liquid chloroform, represented fumigated sample. Another set of soil samples without using chloroform, represented unfumigated samples and soil microbial biomass was estimated from these samples. MB-C, MB-N, and MB-P were higher by 66%, 31%, and 9%, respectively, in HSF than TSF. Distinct seasonality was observed in soil microbial biomass. It was maximum in summer and minimum in rainy season in both the forest stands. The value decreased from summer to rainy season by 46 to 67% in HSF and by 32 to 80% in TSF. Higher soil microbial biomass in the summer season may be due to its accumulation in soil when the plant growth and nutrient demand are minimal. Analysis of variance suggested that MB-C, MB-N, and MB-P were significantly different for both sites and seasons (P < 0.001). Soil organic carbon, TN, and TP were positively correlated with MB-C, MB-N, and MB-P in both the forests. In conclusion, the higher value of soil microbial biomass in HSF may be due to the higher concentration of soil organic matter and decreasing turnover rate of microbial biomass due to higher altitude. On the other hand, the lower value of microbial biomass at TSF may indicate its fast turnover rate due to lowland tropics to enhance the nutrient cycling process.